1991
DOI: 10.1302/0301-620x.73b6.1659570
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable pin fixation of elbow fractures in children. A randomised trial

Abstract: A prospective randomised clinical trial was undertaken to compare biodegradable polyglycolic acid pins with standard Kirschner wires used to fix displaced elbow fractures in children. Twenty-four children were enrolled in the trial; 14 had fractures of the lateral condyle of the humerus, eight of the medial epicondyle and two had olecranon fractures. Eleven fractures were fixed with Kirschner wires and 13 with polyglycolic acid pins. Fracture union with full function occurred in all cases within six months. Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 0 publications
2
22
1
1
Order By: Relevance
“…These types of absorbable screws and pins have been gaining widespread clinical use, particularly in cases where high mechanical stiffness or strength was not required. Pertinent orthopedic areas might include the knee [280][281][282], shoulder, foot and ankle [283,284], hand, wrist [285], elbow [286], pelvis, and zygomatic fractures. In some other cases, high performance PLA is needed and it was found quite challenging to achieve.…”
Section: Orthopedic and Fixation Devicesmentioning
confidence: 99%
“…These types of absorbable screws and pins have been gaining widespread clinical use, particularly in cases where high mechanical stiffness or strength was not required. Pertinent orthopedic areas might include the knee [280][281][282], shoulder, foot and ankle [283,284], hand, wrist [285], elbow [286], pelvis, and zygomatic fractures. In some other cases, high performance PLA is needed and it was found quite challenging to achieve.…”
Section: Orthopedic and Fixation Devicesmentioning
confidence: 99%
“…These types of absorbable screws and pins have been gaining the widespread clinical use, particularly in cases where high mechanical stiffness or strength was not required. Pertinent orthopedic areas might include the knee [89][90][91], shoulder, foot and ankle [92][93][94], hand, wrist [95], elbow [96], pelvis, and zygomatic fractures. In some cases, high performance PLA was needed, so that techniques would be used to improve the mechanical properties of PLA, particularly impact strength, tensile strength, and flexural strength in fracture fixation, where both metal and biodegradable plate, pins, and rods had limits in their use in fracture fixation.…”
Section: Orthopedic Devicementioning
confidence: 99%
“…Consequently, stress shielding happens and results in bone resorption and wire loosening. In addition to stress shielding effect as well as need for the second surgery, K-wires may cause percutaneous pin tract infection and wire migration [84,85]. Table 2.…”
Section: Permanent Metallic Wiresmentioning
confidence: 99%
“…The wires made of biodegradable synthetic polymers were applied in the fracture fixation of the knee [91], wrist [92], elbow [84] olecranon and patella [93] and small bones of hand [90] and their usage were compared with the metallic K-wires. It was concluded that in both cases the healing time was the same and polymeric wires were suitable alternatives for the metallic ones [84,90,91,93]. Despite the high cost of polymeric biomaterials, the total expenses of treatment by polymeric wires was estimated lower than the metallic ones, since there is no need for the second surgery [93].…”
Section: Biodegradable Polymeric (Bp) Wiresmentioning
confidence: 99%